Effects of repetitive transcranial magnetic stimulation in performing eye–hand integration tasks: Four preliminary studies with children showing low-functioning autism. (August 2014) - Panerai, Simonetta; Tasca, Domenica; Lanuzza, Bartolo; Trubia, Grazia; Ferri, Raffaele; Musso, Sabrina; Alagona, Giovanna; Di Guardo, Giuseppe; Barone, Concetta; Gaglione, Maria P; Elia, Maurizio
This report, based on four studies with children with low-functioning autism, aimed at evaluating the effects of repetitive transcranial magnetic stimulation delivered on the left and right premotor cortices on eye–hand integration tasks; defining the long-lasting effects of high-frequency repetitive transcranial magnetic stimulation; and investigating the real efficacy of high-frequency repetitive transcranial magnetic stimulation by comparing three kinds of treatments (high-frequency repetitive transcranial magnetic stimulation, a traditional eye–hand integration training, and both treatments combined). Results showed a significant increase in eye–hand performances only when high-frequency repetitive transcranial magnetic stimulation was delivered on the left premotor cortex; a persistent improvement up to 1 h after the end of the stimulation; better outcomes in the treatment combining high-frequency repetitive transcranial magnetic stimulation and eye–hand integration training. Based on these preliminary findings, further evaluations on the usefulness of high-frequency repetitive transcranial magnetic stimulation in rehabilitation of children with autism are strongly recommended.